Dual Drug Loaded, pH-Sensitive Metal-Organic Particles for Synergistic Cancer Therapy - Wu, Shichao; Hu, Shuo; Yang, Xiangrui (Frontiers in Bioengineering and Biotechnology, 2022)
The strategy for dual drug-loaded nanomedicine with targeting properties was always complex. Herein, a novel strategy for the preparation of metal-organic particle-based nanomedicine has been developed, and combretastatin A4 (CA4) and mitoxantrone (MIT) loaded MOPs (CMMOPs) have been obtained. In this system, using merely Cu(II) as a bridge to connect and coordinate with the dual drugs has resulted in the CMMOPs possessing a fairly high drug load of almost 90%. Moreover, the coordination between Cu(II) and the drugs was stable at physiological pH but easily cleavable in the tumor acidic microenvironment, which would provide a good targeting property for CMMOPs. The in vivo experiments indicated that CMMOPs possessed a significantly enhanced antitumor efficiency with negligible side effects. The results suggest that CMMOPs could be a potential anticancer formulation for tumor-targeted drug delivery.